Peran Pendidikan Agama Islam dalam Membentuk Akhlak : (Studi Kasus Siswa Siswi SDN Tamanayu 01) - Imroatus Sholihah; Mudhofar Mudhofar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the ways in which Islamic Religious Education (PAI) influences the moral growth of Tamanayu 01 Elementary School pupils. Given the difficulties presented by the digital age and shifting societal norms, moral development has become an essential part of basic education. This study combined a case study methodology with a qualitative technique. Observation, in-depth interviews, and documentation with the administrator, parents, instructors, and children were used to collect the data. The findings demonstrated that Tamanayu 01 Elementary School's implementation of PAI was done in a comprehensive way by incorporating Islamic values into the curriculum, holding regular religious events like congregational prayer and sermons, and encouraging teacher cooperation to create a religious school culture. In addition to cognitive dimensions, learning also addressed pupils' emotive and psychomotor aspects. Significant supporting factors included the commitment of the principal and teachers, family and community support, and the availability of infrastructure. However, the process of moral formation also faced obstacles such as limited time for PAI learning, the negative influence of social media, the diversity of student backgrounds, and limited resources. According to the study's findings, PAI plays a strategic role in forming students' personalities through an all-encompassing, contextual, and cooperative approach. It is anticipated that other elementary schools will use these findings as a guide when creating character education programmes based on Islamic principles.